Feasibility and accuracy of fetal echocardiography at routine 11 to 13 weeks 6 days ultrasound performed on unselected obstetric population in a tertiary maternity centre with high patient turnover - Poojari, Vidyashree G.; Reddy, Arevidya; Vasudeva, Akhila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Congenital heart defects (CHD) remain the most prevalent congenital malformations, with an estimated prevalence of 6-8 per 1000 live births. Routinely, fetal echo is performed around 18-22 weeks among high risk cases. A dedicated early fetal echo (EFEC) performed by experts between 11-16 weeks is emerging as an excellent screening tool among high risk cases. However, feasibility of obtaining such cardiac views during routine Nuchal Translucency scan by trained obstetricians, is yet to be known as there is limited time available with high patient turn over. Present study aimed to know the feasibility and accuracy of EFEC in unselected obstetric population in a tertiary maternity centre with high patient turnover. Methods: This was an observational cohort study from March 2015 to April 2017 at a tertiary maternity referral hospital. Singleton pregnant women undergoing routine 11-13+6 weeks scanning (NT scan) were recruited in the study including both high and low risk pregnancies. Possibility of obtaining 4 basic cardiac views within this limited time was assessed. Results: A total of 180 early fetal ECHO’s were performed during the course of this study. The 4-chamber view (79.44%) of the heart was the easiest parameter to visualize. RVOT (28.88%) was the most difficult view to be obtained. Complete visualization of all the cardiac views was possible in only 34 women (18.88%). The visualization rates of the cardiac views improved as the gestational age increased. TVS was essential to obtain cardiac views in 5 cases out of 138 (3.6%) in 12-13+6 scans. Whereas, TVS was essential to visualize cardiac views in 34 cases out of 42 (80.95%) between 11 weeks to 11 weeks 6 days. A total of 7 cardiac anomalies were detected during this study. There were 3 major and 4 minor cardiac malformations. Out of the 3 major anomalies, 2 were AVSDs which were diagnosed by EFEC. Minor defects were undetected. Conclusions: It is feasible to get the basic cardiac views in the limited time available to perform NT scan among unselected obstetric population in a tertiary maternity centre with a high turnover. Gestational age of 12 weeks and above seems to increase the accuracy. TVS is a useful adjunct throughout 11-14 weeks scan.